Effect of Domestic Violence on Family Stability in Tumboboi Parish, Kapchorwa District - Davis Chebet (Uganda Christian University, 2025)
This study examined the effect of domestic violence on family stability in Tumboboi Parish, Kapchorwa District, guided by three objectives: to identify the root causes of domestic violence, assess its effects on family stability, and evaluate strategies for its mitigation. Using a descriptive design, data was collected from a sample of 63 respondents through questionnaires and interviews and analyzed using SPSS version 23 with descriptive statistics and thematic analysis. Findings revealed that key causes included financial stress, substance abuse, patriarchal cultural beliefs, poor communication skills (61%) and childhood exposure to violence (62%). The effects on family stability were profound, with 80% noting that children in violent homes suffer anxiety and depression and 57% linking abuse-related trauma to economic instability. While strategies such as community sensitization, legal enforcement, counseling, economic empowerment, and safe shelters were identified, 60% of respondents doubted sensitization alone could shift harmful norms. The study concludes that domestic violence in Tumboboi Parish is a multidimensional challenge requiring integrated legal, psychosocial, economic, and culturally sensitive interventions to restore family cohesion, wellbeing, and stability.